Numerical study on the influence of installation effect on laterally loaded piles in sand - SU Dong; WU Zexiong; LEI Guoping; WANG Shun (Shenzhen Daxue xuebao. Ligong ban)
In order to study the influence of the installation effect caused by pile penetration into a sand foundation on the pile horizontal bearing capacity, we establish a numerical model to simulate the penetration process and the horizontal loading process of the pile and analyze the response of pile. The whole process of pile penetration is simulated using the arbitrary Lagrangian-Euler (ALE) technology and a state-dependent dilatancy sand constitutive model, and compared with the model test. Through coordinate conversion and interpolation, the soil state data of the axisymmetric ALE model is transferred to a three dimensional Lagrangian finite element model for horizontal loading research. In order to quantitatively study the influence of the installation effect, the laterally loaded pile without the installation effect is simulated simultaneously. The results show that the compaction effect after pile penetration is related to the relative density of sand. Sand loosening has been observed in shallower locations for piles in relatively dense sand. The penetration of piles also improves the level of lateral soil stress. In loose sand, the lateral soil resistance-pile displacement curves of piles with installation effect are generally higher than that without installation effect. However, opposite observations have been made for the shallow layers of dense sand. The installation effect can greatly improve the lateral bearing capacity of the relatively short piles in loose sand, and on the contrary, it reduces the lateral bearing capacity of long piles in dense sand. The change rate of the lateral bearing capacity after considering the installation effect is negatively correlated to the relative sand density, which shows a strong linear relationship for long piles. This study can provide reference for predicting the horizontal bearing capacity of a displacement pile.